Effect of Epigallocatechin Gallate on Cadmium Chloride-induced Oxidative Stress in Female Sprague Dawley Rats - Parasuraman, Subramani; Beng, James Yu Kar; Hui, Lam Chew; Qin, Brenda Ngu Yen (Free Radicals and Antioxidants)
Background: Epigallocatechin gallate (EGCG) is the ester of epigallocatechin and gallic acid. EGCG is abundant in dry tea leaves and its effect on heavy metal-induced oxidative stress is not clear. Hence, the present study is planned to study the effect of EGCG on cadmium chloride (CdCl2) induced oxidative stress in female Sprague Dawley rats. Methods: The rats were divided into six groups with each of six animals viz., control, CdCl2, vitamin C, EGCG, CdCl2 + vitamin C and CdCl2 + EGCG. CdCl2 (5 mg/kg) was suspended in carboxymethyl cellulose and administered orally to induce oxidative stress. Vitamin C and EGCG were dissolved in sterile water for injection and administered intraperitoneally within 15 min after CdCl2 administration. All the animals were administered with respective assigned treatment once daily for 28 consecutive days. At the end of the study, blood samples were collected from all the animals and serum was separated. The serum sample was used for biochemical analysis. Later, the rats were sacrificed and liver samples were collected and used for antioxidant assay. Results: EGCG and vitamin C prevented the CdCl2-induced oxidative stress. CdCl2 administered group showed significant increases in the levels of glucose, AST, ALT and urea when compared with control group, whereas vitamin C and EGCG prevented the CdCl2-induced biochemical changes. Vitamin C and EGCG also prevented the CdCl2-induced reduction in levels of reduced glutathione and catalase. Conclusion: EGCG had significant ameliorative effect on CdCl2 -induced oxidative stress in experimental animals.
Keywords: Cadmium; Catalase; Catechin; Glutathione; Vitamin C